Parenting Device Management in Developing Parental Educational Awareness - Dwi Nugroho Hidayanto; Nurlaili; Titi Dwi Jayanti (Didaktika: Jurnal Kependidikan, 2025)
This study aims to obtain parental insight data on the management of gadgets through parenting carried out in the Anak Bangsa Kindergarten and to awaken parents’ education consciousness. The research uses Mixed Methods with an Explanatory Design. Starting from the quantitative method first in full both at the stage of data collection, data analysis and results, and then entering the mixed method, where the quantitative results of 14 respondents are needed for clarification in selecting participants or research subjects as many as 3 people. Enter the qualitative method, namely by collecting data, analyzing data, and results. Interpretation emphasizes quantitative results where qualitative results serve to explain and elaborate quantitative results. The results of the study show that the majority of parents of Anak Bangsa Kindergarten students are very familiar with the principles of education (44%), very well understood with the positives and negatives of gadget use (43%), very well understood with the concept of gadget management (81%), and very well understood with the application of gadget management (86%). Qualitatively, through in-depth interviews, it shows that they have a good understanding of parenting and gadget management and have implemented effective strategies and solutions from what they understand: understand the three domains of education; understand the positive and negative sides of gadget use; understand the concept of gadget management, and; understand in implementing gadget management. The study found that the consistency of understanding and actions of gadget management is paradoxical with the results of previous research, namely the inconsistency of parental understanding obtained from parenting the use of gadgets with their daily application. The conclusion of this research narrows down to one novelty, namely the idea that a combination of three sciences (psychology, sociology, pedagogy) is needed to become a frame in gadget management and to observe further and delve deeper into the phenomenon of consistency and inconsistency of parenting in gadget management.